2017
DOI: 10.1590/s1678-9946201759077
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and antimicrobial susceptibility of thermophilic Campylobacter species isolated from healthy children attending municipal care centers in Southern Ecuador

Abstract: The prevalence and antimicrobial susceptibility of Campylobacter jejuni and C. coli strains in healthy, well-nourished children of middle socioeconomic level from Southern Ecuador were determined. Among the 127 children studied, 17 (13.4%) harbored Campylobacter sp. corresponding to C. jejuni (7.1%) and C. coli (6.3%) with a higher concentration of C. jejuni among boys (8.6%) and C. coli (8.8%) among girls. C. jejuni showed high resistance to nalidixic acid and ciprofloxacin (77.8%), but susceptibility to all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…All of the strains, except one strain of C jejuni, were susceptible to gentamycin and amoxicillin-clavulanic acid. In previous studies conducted in Southern Ecuador, no resistance was observed in either C. jejuni or in C. coli strains isolated from dogs (TOLEDO et al, 2015), backyard chickens (OCHOA et al, 2016) and healthy children (TOLEDO et al, 2017). All of the amoxicillin-resistant strains were cefinase positive and susceptible to amoxicillin-clavulanic acid and are, therefore, beta-lactamase producers (IOVINE, 2013), with the exception of one strain of C. jejuni that remained resistant.…”
Section: Animals Of Origin (N)mentioning
confidence: 87%
See 1 more Smart Citation
“…All of the strains, except one strain of C jejuni, were susceptible to gentamycin and amoxicillin-clavulanic acid. In previous studies conducted in Southern Ecuador, no resistance was observed in either C. jejuni or in C. coli strains isolated from dogs (TOLEDO et al, 2015), backyard chickens (OCHOA et al, 2016) and healthy children (TOLEDO et al, 2017). All of the amoxicillin-resistant strains were cefinase positive and susceptible to amoxicillin-clavulanic acid and are, therefore, beta-lactamase producers (IOVINE, 2013), with the exception of one strain of C. jejuni that remained resistant.…”
Section: Animals Of Origin (N)mentioning
confidence: 87%
“…Following collection, each fecal sample was inoculated onto a transport-enrichment medium (FERNÁNDEZ, 1992) consisting of (composition/L) Brucella broth 28g, agar 1.5g, sodium metabisulphite 0.5g, ferrous sulphate 0.5g, sodium pyruvate 0.5g, trimethoprim 10mg, rifampicin 15mg, colistin 10,000IU, amphotericin 10mg and horse blood 30mL, and transported to the laboratory under a microaerobic atmosphere obtained using commercial generator envelopes (FERNÁNDEZ, 1992;TOLEDO et al 2017). After an enrichment period of 24h at 42°C under microaerobic conditions, aliquots of each enriched sample were seeded on Butzler medium plates and incubated for 48h under the same conditions described above.…”
mentioning
confidence: 99%
“…Acknowledged the fine line while distinguishing between veterinary-and human-pathogens, the following paragraphs aim at describing the major bacterial specimens responsible of relevant domestic animal infections and their contribution to the overall AMR onset and diffusion (Table 1). Campylobacter spp are a group of spiral-shaped Gram-negative bacteria responsible for gastrointestinal infections in several domestic animals, such as cattle, chicken, turkey, pig, sheep, and pets, including dogs and cats [91,92]. The prevalent aetiologic agent is Campylobacter jejuni, but all Campylobacter isolates have demonstrated resistance against one or more antimicrobial compound(s) including quinolones, macrolides, lincosamides, chloramphenicol, aminoglycosides, tetracycline, β-lactams, cotrimoxazole, and tylosin [93][94][95].…”
Section: Microorganisms Involved In Relevant Domestic Animal Infectionsmentioning
confidence: 99%
“…This information is necessary for the fundamental correlation of the numbers of bacteria detected by culture (and culture-independent tests) with clinical diarrheal symptoms. Such an estimate will be also be useful for study of protective immunity [ 26 ] or asymptomatic carriage [ 5 , 6 ] of Campylobacter spp., especially in endemic settings.…”
Section: Introductionmentioning
confidence: 99%